Oral lesions after COVID-19 vaccination: Immune mechanisms and clinical approach - Mohammad Amin Khazeei Tabari; Shaghayegh Najary; Gita Khadivi; Mohammad Javad Yousefi; Noosha Samieefar; Fahimeh Abdollahimajd (Infectious Medicine, 2022)
COVID-19 vaccination, although is a promising tool to overcome the pandemic, has side effects. There are increasing reports of oral lesions after COVID-19 vaccination. The aim of this review is to identify the occurrence of some oral lesions after COVID-19 vaccination, and highlight the underlying immune mechanisms involved. A narrative literature review was performed by searching electronic databases including PubMed, Scopus and Web of Science to investigate the oral lesions after COVID-19 vaccination. The inclusion criteria were original studies, including the case reports, case series, letter to the editor, and cross-sectional studies. The exclusion criteria included the studies which examined the oral lesions caused by COVID-19 infection. The information, including the number of participant(s) receiving vaccine, type of vaccine, dose number, side effect(s), time of onset following vaccination, healing time, treatment strategies for the existing lesions, and related mechanisms were then summarized in a data extraction sheet. The results of this review showed that some vaccines had side effects with oral involvement such as pemphigus vulgaris, bullous pemphigoid, herpes zoster, lichen planus, Stevens-Johnson syndrome and Behçet's disease. Future research needs to elucidate the physiopathology of oral manifestations after the COVID-19 vaccination, and better understand the risk factors associated with such responses. Sometimes vaccine's side effects may be due to the nocebo effect, which means that the person expects some adverse events to occur following the vaccine administration.